Clinical implications of respiratory ciliary dysfunction in heterotaxy patients with congenital heart disease: elevated risk of postoperative airway complications - Zhao, Tingting; Huang, Xianghui; Chen, Weicheng; Gao, Han; Feng, Zhiyu; Tan, Chaozhong; Sun, Jingwei; Ma, Xiaojing; Yan, Weili; Sheng, Wei; Huang, Guoying (Frontiers in Cardiovascular Medicine, 2024)
Cardiac surgery in Congenital Heart Disease-Heterotaxy (CHD-HTX) patients often leads to increased postoperative airway complications. Abnormal respiratory ciliary function, resembling primary ciliary dyskinesia, has been observed. We expanded the sample size by retrospectively reviewing Ciliary Dysfunction (CD) in CHD-HTX patients to verify the increased risk of post-surgical respiratory complications.We conducted a retrospective review of 69 CHD-HTX patients undergoing cardiac surgery, assessing abnormal respiratory function using nasal nitric oxide (nNO) levels and nasal ciliary motion observed in video microscopy. Data collected included demographics, surgical details, postoperative complications, length of stay, ICU hours, salvage procedures, intubation duration, and mortality.The CD and no-CD cohorts exhibited notable similarities in risk adjustment in Congenital Heart Surgery-1 (RACHS-1) risk categories, age at the time of surgery, and the duration of follow-up evaluations. We observed a trend toward an increased length of post-operative stay in the CD group (15.0 vs 14.0; P=0.0017). CHD-HTX patients with CD showed significantly higher rates of respiratory complications (70% vs 44.4%; P=0.008). There were no notable variances observed in postoperative hospitalization duration, mechanical ventilation period, or surgical mortality.Our findings suggest that CHD-HTX patients with CD may face an elevated risk of respiratory complications. These results offer guidance for perioperative management and serve as a reference for further pathological studies.